Migration, labor markets, and integration of migrants: An overview for Europe - Rainer Münz (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
This paper discusses the size of Europe's migrant population, its demographic structure, and the socio-economic position of migrants. The European Labour Force Survey (LFS) as well as Eurostat, OECD and UN migration data are used as the main databases. In most sections of the paper the geographic unit of analysis is EU 15 as the so-called old EU Member States are home or host some 94 percent of all migrants and some 97 percent of all legal foreign residents living in EU 27. But general information on stocks of international migrants and recent migration flows are given for all countries of Western, Central and South-Eastern Europe.
Keywords: 330